A Systematic Review on the Role of the Respiratory and Intestinal Mucosal Immunity during Newcastle Disease Virus Infection - Mohd Iswadi Ismail (WARTAZOA. Indonesian Bulletin of Animal and Veterinary Sciences, 2022)
Newcastle disease (ND) is a devastating disease causing substantial economic losses due to high morbidity and mortality events worldwide in poultry. The disease is caused by the Newcastle disease virus (NDV), an enveloped, non-segmented single strand of negative-sense RNA approximately 15 kb in length. NDV can be classified as asymptomatic, lentogenic, mesogenic or velogenic pathotypes based on the levels of pathogenicity in chickens. The disease is being controlled by vaccination using either live-attenuated or inactivated vaccines. Various studies have been conducted to evaluate the association between mucosal immunity on NDV, however, the contribution of role of either respiratory or intestinal mucosal immunity remains to be revealed. Thus, the current study aimed to systematically review published articles about the role of respiratory and intestinal mucosal immunity during NDV infection. An online database search was performed through four different databases namely PubMed, Science Direct, JSTOR and Google Scholar using the following set of keywords: ‘Newcastle disease’, ‘Newcastle disease virus’, ‘respiratory’, ‘intestinal’ and ‘mucosal immunity’. Out of the 34,142 results, only 28 articles were suitable according to inclusion and exclusion criteria and were used for data extraction. Results showed that innate immunity was the most affected parameter when exposed to NDV infections, however, the role of respiratory and intestinal mucosal immunity against NDV infection remains widely uncharted. In conclusion, the role of the sub-components of respiratory and intestinal mucosal immunity toward NDV infection may become one of the determinant factors of protection for the chickens.